Aberrant Expression of miR-362 Promotes Lung Cancer Metastasis through Downregulation of Sema3A - Dan Luo; Zheng Zhang; Zhao Zhang; Jia-Yue Li; Jian Cui; Wen-Pu Shi; Xi-Wen Dong; Lin Yuan; Peng Lin; Zhi-Nan Chen; Hui-Jie Bian; Zi-Ling Wang (Journal of Immunology Research)
miR-362 is a recently discovered member of the microRNA family, and it modulates a variety of physical activities and plays an important role in the occurrence and development of many tumors. However, the biological functions of hsa-miR-362-5p in non-small-cell lung carcinoma (NSCLC) are unknown. Transwell assay and colony formation were used to determine the migration, invasion, and proliferation of NSCLC cells in vitro. A subcutaneous tumor model in nude mice was established to detect NSCLC tumor growth in vivo. The direct binding of miR-362 to the 3′UTR of Semaphorin 3A (Sema3A) was confirmed by luciferase reporter assay. In this study, we found that the level of miR-362 was higher in NSCLC tissues than in adjacent normal tissues and that the level of miR-362 expression was also elevated in five NSCLC cell lines (A549, 95-D, H1299, H292, and H460) relative to a human normal lung epithelial cell line (BEAS2B). Furthermore, miR-362 promoted NSCLC cell invasion, migration, and colony formation in vitro and tumor formation in vivo. Next, we identified the miR-362 target gene Sema3A, which is significantly correlated with metastasis. Sema3A expression was increased in normal tissues relative to NSCLC tissues. This result is consistent with the fact that miR-362 expression is negatively correlated with Sema3A expression in clinical tissue samples and indicated that miR-362 can regulate Sema3A expression in NSCLC cells and consequently affect NSCLC invasion, migration, and colony formation. Taken together, these findings on the newly identified miR-362/Sema3A axis elucidate the molecular mechanism of NSCLC invasion and migration and could lead to a potential therapeutic target in NSCLC treatment.